Performance of 256QAM in LTE-Hi indoor scenario - Shan LIU; Cheng TAO; Liu LIU (Dianxin kexue)
In order to solve the traffic explosion of indoor and hotspots,LTE-Hi was put forward by 3GPP organization in Release12.Due to the coverage particularity of indoor and hotspots scenarios,the organization introduced 256QAM to improve system performance.According to the 256QAM constellation given in the standard,a soft demodulation algorithm based on border distance decision was deduced.Through a simulation of the UE SINR distribution in the LTE-Hi scenario,the feasibility of the 256QAM was proved and according to the CQI/MCS/TBS signaling table changed for 256QAM,link level simulation showed the 256QAM and 64QAM throughput in comparison under different EVM index.Finally,the system performance with and without the introduction of 256QAM under different scenarios was evaluated.